Autoactivation of the MDM2 E3 Ligase by Intramolecular Interaction - Cheng, Qian (American Society for Microbiology, 2014)
The RING domain ubiquitin E3 ligase MDM2 is a key regulator of p53 degradation and a mediator of signals that stabilize p53. The current understanding of the mechanisms by which MDM2 posttranslational modifications and protein binding cause p53 stabilization remains incomplete. Here we present evidence that the MDM2 central acidic region is critical for activating RING domain E3 ligase activity. A 30-amino-acid minimal region of the acidic domain binds to the RING domain through intramolecular interactions and stimulates the catalytic function of the RING domain in promoting ubiquitin release from charged E2. The minimal activation sequence is also the binding site for the ARF tumor suppressor, which inhibits ubiquitination of p53. The acidic domain-RING domain intramolecular interaction is modulated by ATM-mediated phosphorylation near the RING domain or by binding of ARF. These results suggest that MDM2 phosphorylation and association with protein regulators share a mechanism in inhibiting the E3 ligase function and stabilizing p53 and suggest that targeting the MDM2 autoactivation mechanism may be useful for therapeutic modulation of p53 levels.